High Adhesion Superhydrophobic Surface Constructed by PDMS-co-PMHS Coatings Embedded with SiO2 Particles. Issue 3 (May 2021) - Zhang, Wei; Hao, Shang; Chen, Mingyang; Yang, Bo; Xie, Yuan; Zhang, Xingmin; Yao, Jiming
Superhydrophobic surfaces have attracted attention due to their hydrophobic, self-cleaning, anti-icing, and oil/water separation properties. The present study used a nonwoven fabric as a flexible substrate and constructed a high-adhesive superhydrophobic surface by coating the fabric with polydimethylsiloxane (PDMS)- co -polymethyl hydrogen siloxane (PMHS) polymers and embedding mesoporous SiO2 nanoparticles. The water contact angle (WCA) of the superhydrophobic surface was up to 165.2° at a PDMS to PMHS ratio of 4:1. The adhesion to deionized water was 99.7 μN. High hydrophobicity was maintained, even after sandpaper abrasions and flowing water impact. The surface was resistant to acid, alkali, brine, strong oxidation, and heavy metal solutions. The coating exhibited anti-icing and oil/water separation properties. This study provides a facile and effective method for constructing multifunctional superhydrophobic coatings on flexible substrates.